Separation of GVL from GVHD -location, location, location - Teshima, Takanori; Hashimoto, Daigo (Frontiers in Immunology, 2023)
Allogeneic hematopoietic cell transplantation (HCT) is a curative therapy for various hematologic malignancies. However, alloimmune response is a double-edged sword that mediates both beneficial graft-versus-leukemia (GVL) effects and harmful graft-versus-host disease (GVHD). Separation of GVL effects from GVHD has been a topic of intense research to improve transplant outcomes, but reliable clinical strategies have not yet been established. Target tissues of acute GVHD are the skin, liver, and intestine, while leukemic stem cells reside in the bone marrow. Tissue specific effector T-cell migration is determined by a combination of inflammatory and chemotactic signals that interact with specific receptors on T cells. Specific inhibition of donor T cell migration to GVHD target tissues while preserving migration to the bone marrow may represent a novel strategy to separate GVL from GVHD. Furthermore, tissue specific GVHD therapy, promoting tissue tolerance, and targeting of the tumor immune microenvironment may also help to separate GVHD and GVL.